2002
DOI: 10.1080/09603100110050743
|View full text |Cite
|
Sign up to set email alerts
|

Testing for cointegration between international stock prices

Abstract: This paper re-examines the evidence for cointegration between international stock prices. It applies Johansen's maximum likelihood (ML) cointegration method and likelihood ratio (LR) tests for cointegration to stock prices. In monthly data it finds at most one cointegrating vector and in quarterly data finds no cointegrating vectors. Using the small-sample corrections or the small-sample critical values it finds no evidence of cointegration. Johansen's LR tests for cointegration are sensitive to the lag length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 22 publications
1
23
0
1
Order By: Relevance
“…The rank tests thus provides evidence for cointegration between the stock prices in our sample and is consistent with findings of capital markets integration noted by Korajczyk (1996) and Forbes and Rigobon (2002). This finding contrasts with that of Ahlgren and Antell (2002) Lag selection is more complicated, since selection criteria suggest two, fifteen, and sixteen (the maximum) lags. We choose the most parsimonious specification of these: two lags.…”
Section: Cointegrating Rank and Lag Lengthsupporting
confidence: 34%
“…The rank tests thus provides evidence for cointegration between the stock prices in our sample and is consistent with findings of capital markets integration noted by Korajczyk (1996) and Forbes and Rigobon (2002). This finding contrasts with that of Ahlgren and Antell (2002) Lag selection is more complicated, since selection criteria suggest two, fifteen, and sixteen (the maximum) lags. We choose the most parsimonious specification of these: two lags.…”
Section: Cointegrating Rank and Lag Lengthsupporting
confidence: 34%
“…In their study Caporale et al (2009) analysed the stock markets of Germany, France, the Netherlands, Ireland, and the United Kingdom for the sample period between 1973 and 2008, but they did not find any evidence of cointegration. Also using the cointegration Johansen approach, other studies have concluded to the contrary, failing to identify a long-term relationship between stock markets (Li 2006;Olusi and Abdul-Majid 2008;Karim et al 2010) or identifying very faint signs (Ahlgren and Antell 2002). According to Bley (2009), the occurrence of mixed results is strongly influenced by time and country factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies such as Kasa (1992), Arshanapalli and Doukas (1993), Masih (1997, 1999), Francis and Leachman (1998), Ahlgren and Antell (2002), and Syriopoulos (2004, 2007 found that stock markets are interdependent and there is a long term relationship between them. On the other hand, other studies such as Kanas (1998), Huang et al (2000, Climent and Meneu (2003), Gupta and Guidi (2012), Zhang and Li (2014) argue that there is no co-integration.…”
Section: Literature Reviewmentioning
confidence: 99%